TANTANGAN DAN PEMBAHARUAN MUHAMMADIYAH DALAM DUNIA PENDIDIKAN ISLAM - Muna Hajita (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
This paper explores the fil-Islam renewal movement, its existence, the challenges faced by Muhammadiyah, both the development of educational institutions, the education system, education modernization, education management and the challenges of the globalization era for Islamic religious education. This study uses a qualitative study method with a type of literature study. The results of this writing aim to analyze, describe and provide interpretations of the existence, challenges and renewal of Muhammadiyah in the world of Islamic Education. Muhammadiyah is a social organization that is known as one of the pioneers of reforming Islamic Education in Indonesia which is still surviving and even experiencing very rapid quantitative development. As for the discussion is the Existence of Muhammadiyah, problems and challenges as well as renewal of Muhammadiyah.